Modern psychological consultation, its types and reasons for applying to it (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, what is a modern psychological consultation, what are its stages and rules, the types of modern psychology today, and who appeals to a psychologist, why do we need a psychologist in life? - such questions are answered